Effectiveness of domiciliary rehabilitation, telerehabilitation, and home exercise program on pain, function, and quality of life in patients with total knee arthroplasty: A randomized controlled trial - Shrihari L Kulkarni; Sweta Kulkarni; Arvind D Patil; Shefali Anand Painginkar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Knee osteoarthritis (OA) is the major source of disability worldwide. OA of knee is a joint disease that affects the elderly. It is characterized by progressive articular cartilage damage which further causes pain and loss of function. Total knee replacement (TKR) is the standard treatment for severe OA knee. Telerehabilitation is one of the new treatment ways and is speedily growing as an alternative for therapies. OBJECTIVES: The objective of this study was to compare the effects of domiciliary rehabilitation, telerehabilitation, and home exercise program on pain, function, and quality of life (QOL) in patients with TKR. MATERIALS AND METHODS: A total of 108 individuals were enrolled as per eligibility criteria during the study period and then were randomly divided into three groups by computer-generated, randomized sequence numbers. The parameters were obtained preoperatively, postoperatively, and at the end of 1 month using the Visual Analog Scale (VAS), Knee Injury and Osteoarthritis Outcome Score, Quality of Well-being, methadone maintenance treatment (MMT), and knee range of motion (ROM) test. P < 0.05 was considered statistically significant. RESULTS: All the three groups showed a reduction in VAS scores and improved function in patients with TKR. QOL and MMT did not prove to be significant in any of the three groups. When ROM was considered, only Groups A and C showed statistical significance whereas Groups A and B showed clinical significance according to the mean difference values. CONCLUSION: All the three modes of rehabilitation among OA patients, i.e., domiciliary rehabilitation, telerehabilitation, and home-based exercise program, have shown similar effects on study variables including pain intensity, knee function, and QOL in patients with TKR. Therefore, we recommend to include telerehabilitation as one of the treatment approaches for patients with TKR whenever needed.